Biological inhibition of soil nitrification by forest tree species affects Nitrobacter populations - Amandine Laffite; Alessandro Florio; Kasaina Sitraka Andrianarisoa; Charline Creuze des Chatelliers; Brigitte Schloter‐Hai; Sidy M. Ndaw; Charlotte Periot; Michael Schloter; Bernd Zeller; Franck Poly; Xavier Le Roux (Environmental Microbiology, 2020)
Summary Some temperate tree species are associated with very low soil nitrification rates, with important implications for forest N dynamics, presumably due to their potential for biological nitrification inhibition (BNI). However, evidence for BNI in forest ecosystems is scarce so far and the nitrifier groups controlled by BNI‐tree species have not been identified. Here, we evaluated how some tree species can control soil nitrification by providing direct evidence of BNI and identifying the nitrifier group(s) affected. First, by comparing 28 year‐old monocultures of several tree species, we showed that nitrification rates correlated strongly with the abundance of the nitrite oxidizers Nitrobacter (50‐ to 1000‐fold changes between tree monocultures) and only weakly with the abundance of ammonia oxidizing archaea (AOA). Second, using reciprocal transplantation of soil cores between low and high nitrification stands, we demonstrated that nitrification changed 16 months after transplantation and was correlated with changes in the abundance of Nitrobacter , not AOA. Third, extracts of litter or soil collected from the low nitrification stands of Picea abies and Abies nordmanniana inhibited the growth of Nitrobacter hamburgensis X14. Our results provide for the first time direct evidence of BNI by tree species directly affecting the abundance of Nitrobacter .

Denitrifying bacterial communities display different temporal fluctuation patterns across Dutch agricultural soils - Nguyen E. López-Lozano; Michele C. Pereira e Silva; Franck Poly; Nadine Guillaumaud; Jan Dirk van Elsas; Joana Falcão Salles (Antonie van Leeuwenhoek, 2017)

Plant species diversity affects soil–atmosphere fluxes of methane and nitrous oxide - Pascal A. Niklaus; Xavier Le Roux; Franck Poly; Nina Buchmann; Michael Scherer-Lorenzen; Alexandra Weigelt; Romain L. Barnard (Oecologia, 2016)

Functional and structural responses of soil N-cycling microbial communities to the herbicide mesotrione: a dose-effect microcosm approach - Olivier Crouzet; Franck Poly; Frédérique Bonnemoy; David Bru; Isabelle Batisson; Jacques Bohatier; Laurent Philippot; Clarisse Mallet (Environmental Science and Pollution Research, 2016)

Identification of B ‐type procyanidins in F allopia spp. involved in biological denitrification inhibition - Clément Bardon; Florence Piola; Feth Zahar Haichar; Guillaume Meiffren; Gilles Comte; Boris Missery; Manon Balby; Franck Poly (Environmental Microbiology, 2016)
Summary Nitrogen ( N ) is considered as a main limiting factor in plant growth, and nitrogen losses through denitrification can be responsible for severe decreases in plant productivity. Recently, it was demonstrated that F allopia spp. is responsible for biological denitrification inhibition ( BDI ) through the release of unknown secondary metabolites. Here, we investigate the secondary metabolites involved in the BDI of F allopia spp. The antioxidant, protein precipitation capability of F allopia spp. extracts was measured in relation to the aerobic respiration and denitrification of two bacteria (Gram positive and Gram negative). Proanthocyanidin concentrations were estimated. Proanthocyanidins in extracts were characterized by chromatographic analysis, purified and tested on the bacterial denitrification and aerobic respiration of two bacterial strains. The effect of commercial procyanidins on denitrification was tested on two different soil types. Denitrification and aerobic respiration inhibition were correlated with protein precipitation capacity and concentration of proanthocyanidins but not to antioxidant capacity. These proanthocyanidins were B ‐type procyanidins that inhibited denitrification more than the aerobic respiration of bacteria. In addition, procyanidins also inhibited soil microbial denitrification. We demonstrate that procyanidins are involved in the BDI of F allopia spp. Our results pave the way to a better understanding of plant–microbe interactions and highlight future applications for a more sustainable agriculture.

Resource pulses can alleviate the biodiversity–invasion relationship in soil microbial communities - Cyrus A. Mallon; Franck Poly; Xavier Le Roux; Irene Marring; Jan Dirk van Elsas; Joana Falcão Salles (Ecology, 2015)
The roles of species richness, resource use, and resource availability are central to many hypotheses explaining the diversity–invasion phenomenon but are generally not investigated together. Here, we created a large diversity gradient of soil microbial communities by either assembling communities of pure bacterial strains or removing the diversity of a natural soil. Using data on the resource‐use capacities of the soil communities and an invader that were gathered from 71 carbon sources, we quantified the niches available to both constituents by using the metrics community niche and remaining niche available to the invader. A strong positive relationship between species richness and community niche across both experiments indicated the presence of resource complementarity. Moreover, community niche and the remaining niche available to the invader predicted invader abundance well. This suggested that increased competition in communities of higher diversity limits community invasibility and underscored the importance of resource availability as a key mechanism through which diversity hinders invasions. As a proof of principle, we subjected selected invaded communities to a resource pulse, which progressively uncoupled the link between soil microbial diversity and invasion and allowed the invader to rebound after nearly being eliminated in some communities. Our results thus show that (1) resource competition suppresses invasion, (2) biodiversity increases resource competition and decreases invasion through niche preemption, and (3) resource pulses that cannot be fully used, even by diverse communities, are favorable to invasion.

Using plant traits to explain plant–microbe relationships involved in nitrogen acquisition - Amélie A. M. Cantarel; Thomas Pommier; Marie Desclos-Theveniau; Sylvain Diquélou; Maxime Dumont; Fabrice Grassein; Eva-Maria Kastl; Karl Grigulis; Philippe Laîné; Sandra Lavorel; Servane Lemauviel-Lavenant; Emmanuelle Personeni; et al. (Ecology, 2015)
It has long been recognized that plant species and soil microorganisms are tightly linked, but understanding how different species vary in their effects on soil is currently limited. In this study, we identified those plant characteristics (identity, specific functional traits, or resource acquisition strategy) that were the best predictors of nitrification and denitrification processes. Ten plant populations representing eight species collected from three European grassland sites were chosen for their contrasting plant trait values and resource acquisition strategies. For each individual plant, leaf and root traits and the associated potential microbial activities (i.e., potential denitrification rate [DEA], maximal nitrification rate [NEA], and NH 4 + affinity of the microbial community [NHS com ]) were measured at two fertilization levels under controlled growth conditions. Plant traits were powerful predictors of plant–microbe interactions, but relevant plant traits differed in relation to the microbial function studied. Whereas denitrification was linked to the relative growth rate of plants, nitrification was strongly correlated to root trait characteristics (specific root length, root nitrogen concentration, and plant affinity for NH 4 + ) linked to plant N cycling. The leaf economics spectrum (LES) that commonly serves as an indicator of resource acquisition strategies was not correlated to microbial activity. These results suggest that the LES alone is not a good predictor of microbial activity, whereas root traits appeared critical in understanding plant–microbe interactions.

A comparison of the strength of biodiversity effects across multiple functions - Eric Allan; Wolfgang W. Weisser; Markus Fischer; Ernst-Detlef Schulze; Alexandra Weigelt; Christiane Roscher; Jussi Baade; Romain L. Barnard; Holger Beßler; Nina Buchmann; Anne Ebeling; Nico Eisenhauer; et al. (Oecologia, 2013)

The effects of snowpack properties and plant strategies on litter decomposition during winter in subalpine meadows - Patrick Saccone; Samuel Morin; Florence Baptist; Jean-Marc Bonneville; Marie-Pascale Colace; Florent Domine; Mathieu Faure; Roberto Geremia; Jonathan Lochet; Franck Poly; Sandra Lavorel; Jean-Christophe Clément (Plant and Soil, 2013)

Four years of experimental climate change modifies the microbial drivers of N 2 O fluxes in an upland grassland ecosystem - Amélie A. M. Cantarel; Juliette M. G. Bloor; Thomas Pommier; Nadine Guillaumaud; Caroline Moirot; Jean‐François Soussana; Franck Poly (Global Change Biology, 2012)
Emissions of the trace gas nitrous oxide ( N 2 O ) play an important role for the greenhouse effect and stratospheric ozone depletion, but the impacts of climate change on N 2 O fluxes and the underlying microbial drivers remain unclear. The aim of this study was to determine the effects of sustained climate change on field N 2 O fluxes and associated microbial enzymatic activities, microbial population abundance and community diversity in an extensively managed, upland grassland. We recorded N 2 O fluxes, nitrification and denitrification, microbial population size involved in these processes and community structure of nitrite reducers ( nir K) in a grassland exposed for 4 years to elevated atmospheric CO 2 (+200 ppm), elevated temperature (+3.5 °C) and reduction of summer precipitations (−20%) as part of a long‐term, multifactor climate change experiment. Our results showed that both warming and simultaneous application of warming, summer drought and elevated CO 2 had a positive effect on N 2 O fluxes, nitrification, N 2 O release by denitrification and the population size of N 2 O reducers and NH 4 oxidizers. In situ N 2 O fluxes showed a stronger correlation with microbial population size under warmed conditions compared with the control site. Specific lineages of nir K denitrifier communities responded significantly to temperature. In addition, nir K community composition showed significant changes in response to drought. Path analysis explained more than 85% of in situ N 2 O fluxes variance by soil temperature, denitrification activity and specific denitrifying lineages. Overall, our study underlines that climate‐induced changes in grassland N 2 O emissions reflect climate‐induced changes in microbial community structure, which in turn modify microbial processes.

Light interception principally drives the understory response to boxelder invasion in riparian forests - Marion Bottollier-Curtet; Jean-Yves Charcosset; Franck Poly; Anne-Marie Planty-Tabacchi; Eric Tabacchi (Biological Invasions, 2012)

Niche construction by the invasive Asian knotweeds (species complex Fallopia): impact on activity, abundance and community structure of denitrifiers and nitrifiers - Nicolas Dassonville; Nadine Guillaumaud; Florence Piola; Pierre Meerts; Franck Poly (Biological Invasions, 2011)

Community niche predicts the functioning of denitrifying bacterial assemblages - Joana F. Salles; Franck Poly; Bernhard Schmid; Xavier Le Roux (Ecology, 2009)
Predicting biodiversity effects on ecosystem functioning requires adequate evaluation of the mechanisms explaining why more diverse systems could perform better than less diverse ones. In this context, tackling functional diversity has become an important issue. Even though the aggregation of species into functional groups supposes niche differences among groups, the concept of niche has not been fully exploited in the context of the biodiversity–ecosystem functioning research. Here we report the results of microcosm experiments where we used bacteria as a model to explore whether niche differences among species provide a good estimation of community functioning. For that we used experimental communities of denitrifying bacterial species and investigated the effects of bacterial diversity on two community processes, denitrification and anaerobic CO 2 ‐production. We first measured the activities of 16 bacterial species grown individually on six different carbon sources. We then used the same set of species to assemble communities varying in both species richness and composition in microcosms containing a mixture of all six carbon sources. The performances of individual species on individual carbon sources were used to calculate, for each process measured, an a priori index called “community niche” that accounted for the performances of the species present in a given community across the entire range of the six resources. We found that species richness had a positive but small effect on both community processes whereas community niche explained a much larger proportion of the variation. According to the results of a path analysis, community niche was the main driver for the corresponding community process, but species richness affected community niche and thus had an indirect effect on denitrification and CO 2 production. In addition to community niche, the presence of particular bacterial species also influenced community functioning, indicating that other effects than the capacity to use carbon sources played a, albeit minor, role in our experiment. Our study provides evidence for the importance of resource niches in shaping biodiversity–ecosystem functioning relationships of bacterial communities.

Decline of soil microbial diversity does not influence the resistance and resilience of key soil microbial functional groups following a model disturbance - Sophie Wertz; Valérie Degrange; James I. Prosser; Franck Poly; Claire Commeaux; Nadine Guillaumaud; Xavier Le Roux (Environmental Microbiology, 2007)
Summary Analysing the consequences of the decrease in biodiversity for ecosystem functioning and stability has been a major concern in ecology. However, the impact of decline in soil microbial diversity on ecosystem sustainability remains largely unknown. This has been assessed for decomposition, which is insured by a large proportion of the soil microbial community, but not for more specialized and less diverse microbial groups. We determined the impact of a decrease in soil microbial diversity on the stability (i.e. resistance and resilience following disturbance) of two more specialized bacterial functional groups: denitrifiers and nitrite oxidizers. Soil microbial diversity was reduced using serial dilutions of a suspension obtained from a non‐sterile soil that led to loss of species with low cell abundance, inoculation of microcosms of the same sterile soil with these serial dilutions, and subsequent incubation to enable establishment of similar cell abundances between treatments. The structure, cell abundance and activity of denitrifying and nitrite‐oxidizing communities were characterized after incubation. Increasing dilution led to a progressive decrease in community diversity as assessed by the number of denaturating gradient gel electrophoresis (DGGE) bands, while community functioning was not impaired when cell abundance recovered after incubation. The microcosms were then subjected to a model disturbance: heating to 42°C for 24 h. Abundance, structure and activity of each community were measured 3 h after completion of the disturbance to assess resistance, and after incubation of microcosms for 1 month to assess resilience. Resistance and resilience to the disturbance differed between the two communities, nitrite oxidizers being more affected. However, reducing the diversity of the two microbial functional groups did not impair either their resistance or their resilience following the disturbance. These results demonstrate the low sensitivity of the resistance and resilience of both microbial groups to diversity decline provided that cell abundance is similar between treatments.

Maintenance of soil functioning following erosion of microbial diversity - Sophie Wertz; Valérie Degrange; James I. Prosser; Franck Poly; Claire Commeaux; Thomas Freitag; Nadine Guillaumaud; Xavier Le Roux (Environmental Microbiology, 2006)
Summary The paradigm that soil microbial communities, being very diverse, have high functional redundancy levels, so that erosion of microbial diversity is less important for ecosystem functioning than erosion of plant or animal diversity, is often taken for granted. However, this has only been demonstrated for decomposition/respiration functions, performed by a large proportion of the total microbial community, but not for specialized microbial groups. Here, we determined the impact of a decrease in soil microbial diversity on soil ecosystem processes using a removal approach, in which less abundant species were removed preferentially. This was achieved by inoculation of sterile soil microcosms with serial dilutions of a suspension obtained from the same non‐sterile soil and subsequent incubation, to enable recovery of community size. The sensitivity to diversity erosion was evaluated for three microbial functional groups with known contrasting taxonomic diversities (ammonia oxidizers nirK genes for denitrifiers, and DGGE analysis of 16S rRNA genes for betaproteobacterial ammonia oxidizers. In addition, we simulated the impact of the removal approach by dilution on the number of soil bacterial species remaining in the inoculum using values of abundance distribution of bacterial species reported in the literature. The reduction of the diversity of the functional groups observed from genetic fingerprints did not impair the associated functioning of these groups, i.e. carbon mineralization, denitrification and nitrification. This was remarkable, because the amplitude of diversity erosion generated by the dilution approach was huge (level of bacterial species loss was estimated to be around 99.99% for the highest dilution). Our results demonstrate that the vast diversity of the soil microbiota makes soil ecosystem functioning largely insensitive to biodiversity erosion even for functions performed by specialized groups.

Effects of management regime and plant species on the enzyme activity and genetic structure of N‐fixing, denitrifying and nitrifying bacterial communities in grassland soils - Ashok K. Patra; Luc Abbadie; Annie Clays‐Josserand; Valérie Degrange; Susan J. Grayston; Nadine Guillaumaud; Pierre Loiseau; Frédérique Louault; Shahid Mahmood; Sylvie Nazaret; Laurent Philippot; Franck Poly; et al. (Environmental Microbiology, 2006)
Summary Management by combined grazing and mowing events is commonly used in grasslands, which influences the activity and composition of soil bacterial communities. Whether observed effects are mediated by management‐induced disturbances, or indirectly by changes in the identity of major plant species, is still unknown. To address this issue, we quantified substrate‐induced respiration (SIR), and the nitrification, denitrification and free‐living N 2 ‐fixation enzyme activities below grass tufts of three major plant species ( Holcus lanatus, Arrhenatherum elatius and Dactylis glomerata ) in extensively or intensively managed grasslands. The genetic structures of eubacterial, ammonia oxidizing, nitrate reducing, and free‐living N 2 ‐fixing communities were also characterized by ribosomal intergenic spacer analysis, and denaturing gradient gel electrophoresis (DGGE) or restriction fragment length polymorphism (RFLP) targeting group‐specific genes. SIR was not influenced by management and plant species, whereas denitrification enzyme activity was influenced only by plant species, and management–plant species interactions were observed for fixation and nitrification enzyme activities. Changes in nitrification enzyme activity were likely largely explained by the observed changes in ammonium concentration, whereas N availability was not a major factor explaining changes in denitrification and fixation enzyme activities. The structures of eubacterial and free‐living N 2 ‐fixing communities were essentially controlled by management, whereas the diversity of nitrate reducers and ammonia oxidizers depended on both management and plant species. For each functional group, changes in enzyme activity were not correlated or were weakly correlated to overall changes in genetic structure, but around 60% of activity variance was correlated to changes in five RFLP or DGGE bands. Although our conclusions should be tested for other ecosystems and seasons, these results show that predicting microbial changes induced by management in grasslands requires consideration of management–plant species interactions.

Nickel mine spoils revegetation attempts: effect of pioneer plants on two functional bacterial communities involved in the N‐cycle - Marina Héry; Laurent Philippot; Eve Mériaux; Franck Poly; Xavier Le Roux; Elisabeth Navarro (Environmental Microbiology, 2005)
Summary Nickel mine spoils in New Caledonia represent an extreme environment, rich in nickel and strongly deficient in elementary elements such as carbon and nitrogen. To rehabilitate these sites, revegetation attempts are performed with endemic plant species establishing dinitrogen‐fixation symbiosis ( Gymnostoma webbianum and Serianthes calycina ). As this biological fixation process provides the major source of available nitrogen in this extreme environment, it could be expected that nitrogen cycling would be stimulated. To study the revegetation effect on mine spoils, the effect of the two pioneer plants on the structure and activity of two functional bacterial communities involved in the N‐cycle was investigated. nifH and narG genes were used as molecular markers for dinitrogen‐fixers and dissimilatory nitrate reducers respectively. In order to assess the influence of the plants on both communities, nine clone libraries were constructed for each targeted gene. Libraries containing 602 and 513 nifH and narG clones, respectively, were screened by restriction fragment length polymorphism (RFLP) analysis. One hundred and forty‐one and 78 representative clones from at least all RFLP families containing more than one clone were sequenced from nifH and narG clone libraries respectively. Both pioneer plants modified the diversity and activity of the two functional communities. However, distinct effects were observed depending on the plant species and the community considered. Serianthes calycina strongly selected a diazotroph phylotype and restored the potential activity of both communities. In contrast, G. webbianum selected no particular phylotype and only restored a fixing activity.

Plant and soil microbial community responses to solid waste leachates diffusion on grassland - Raphaël Gros; Franck Poly; Lucile Jocteur Monrozier; Pierre Faivre (Plant and Soil, 2003)